2006
DOI: 10.1352/0895-8017(2006)111[199:votadi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Autism Diagnostic Interview-Revised

Abstract: The factor structure, internal consistency, and convergent validity of the Autism Diagnostic Interview-Revised (ADI-R) algorithm items were examined in a sample of 226 youngsters with pervasive developmental disabilities. Exploratory factor analyses indicated a three-factor solution closely resembling the original algorithm and explaining 38% of the variance, with one significant discrepancy: Unlike the algorithm, all nonverbal communication items were associated with the Social factor. Internal consistencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 29 publications
6
95
2
Order By: Relevance
“…This grouping of items is based on the clustering of items established by the official ADI-R scoring protocol (Lord et al, 1994), our prior work using this instrument (Seltzer et al, 2003), and recent analysis of the factor structure of the instrument (Lecavalier et al, 2006). The 33rd item was used to determine overall level of language status, which is an independent variable in the analysis described below.…”
Section: Methodsmentioning
confidence: 99%
“…This grouping of items is based on the clustering of items established by the official ADI-R scoring protocol (Lord et al, 1994), our prior work using this instrument (Seltzer et al, 2003), and recent analysis of the factor structure of the instrument (Lecavalier et al, 2006). The 33rd item was used to determine overall level of language status, which is an independent variable in the analysis described below.…”
Section: Methodsmentioning
confidence: 99%
“…The confirmatory factor analyses for two-or three-factor solutions were 'reasonable' [i.e. root-mean-square error of approximation (RMSEA) of ≤ 0.07], 64,67,68 i.e. just above cut-off for a rating of 'good fit'.…”
Section: Autism Diagnostic Interview-revisedmentioning
confidence: 99%
“…Frazier et al 67 indicated that factor structures fit equally well for 2-to 6-year-olds as for those aged ≥ 7 years. Other than testing level of agreement with ADOS (see Autism Diagnostic Observation Schedule, below), only one study 64 explicitly addressed convergent/divergent validity, finding that the ADI-R Social domain correlated with all VABS (-0.41 to -0.45) except for motor skills. A strong indication of validity at the level of individual ADI-R items in distinguishing between children with ASD and those without (mostly non-referred) was provided by Tsuchiya et al 69 Criterion validity was examined in the original Lord et al 63 paper.…”
Section: Autism Diagnostic Interview-revisedmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large-scale factor analysis of autism diagnostic criteria, echolalia did not load on the same factor as other so-called self-stimulatory, restricted, or repetitive behaviors, such as “repetitive use of objects,” “repetitive motor movements” (e.g., hand flapping or finger flicking), or “rituals.” Instead, echolalia loaded on the same factor as other communicative behaviors, including pronoun use (Lecavalier et al 2006), which is why scales of so-called restrictive or repetitive behaviors rarely, if ever, include items assaying echolalia or linguistic repetition (Aman et al 2004, Lam & Aman 2007). …”
Section: Echolalia In Autistic Speechmentioning
confidence: 99%